2020
DOI: 10.1096/fj.201901852rr
|View full text |Cite
|
Sign up to set email alerts
|

Discoidin domain receptor 1 regulates endochondral ossification through terminal differentiation of chondrocytes

Abstract: Chondrocytes in growth plates are responsible for longitudinal growth in long bones during endochondral ossification. Discoidin domain receptor 1 (Ddr1) is expressed in chondrocytes, but the molecular mechanisms by which DDR1 regulates chondrocyte behaviors during the endochondral ossification process remain undefined. To elucidate Ddr1‐mediate chondrocyte functions, we generated chondrocyte‐specific Ddr1 knockout (CKOΔDdr1) mice in this study. The CKOΔDdr1 mice showed delayed development of the secondary ossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
(95 reference statements)
0
17
0
Order By: Relevance
“…Our recent research, investigating the role of Ddr1 in the regulation of EO, has indicated that the chondrocyte-specific Ddr1 knockout can delay the EO and accompany decreased chondrocyte proliferation, terminal differentiation, and apoptosis in growth plates of mice [ 8 ]. Accordingly, we hypothesized that the Ddr1 inhibitor (7 rh) may maintain the survival of articular chondrocytes and reduce the progression of OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent research, investigating the role of Ddr1 in the regulation of EO, has indicated that the chondrocyte-specific Ddr1 knockout can delay the EO and accompany decreased chondrocyte proliferation, terminal differentiation, and apoptosis in growth plates of mice [ 8 ]. Accordingly, we hypothesized that the Ddr1 inhibitor (7 rh) may maintain the survival of articular chondrocytes and reduce the progression of OA.…”
Section: Discussionmentioning
confidence: 99%
“…The Ddr2 ablation reduces the chondrocyte proliferation and thus decreases bone growth; however, the reasons for dwarfism in Ddr1 ablation mice remain unclear. Our recent study using chondrocyte-specific Ddr1 knockout mice demonstrated that the Ddr1 ablation resulted in a decreased chondrocyte proliferation, terminal differentiation, and apoptosis in growth plates and caused a delayed EO [ 8 ]. Our findings indicated that Ddr1 is an imperative regulator of EO in the growth plate and maybe also a potential target for OA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For scanning, the scan settings were an aluminum filter of 0.5 mm, 9 µm scanning resolution, X-ray voltage of 50 kV, X-ray current of 200 mA, and exposure time of 600 ms. The analysis began from the proximal tibia and through the whole fracture site until the distal tibia [19,[21][22][23][24][25][26].…”
Section: Radiographic and µCt Analysesmentioning
confidence: 99%
“…All animal experiments were approved by the Kaohsiung Medical University Animal Care and Use Committee (IACUC105127, 1 August 2017). In our previous work, we generated conditional Ddr1 floxed/floxed mice ( Ddr1 f/f ) [ 33 ]. The inducible a1(I)-collagen-CreERT [B6.Cg.Tg(Col1a1-Cre/ERT2)1Crm/J] cassette contains a 2.3 kb fragment of the Col1a1 promoter, Cre recombinase, ERT2, and polyA and was purchased from Jackson Laboratories.…”
Section: Methodsmentioning
confidence: 99%